Pengaruh Social Media Marketing Dan Brand Awareness Terhadap Minat Beli Produk Skincare MS Glow Pada Generasi Milenial Di Lubuk Pakam - Agnessyah Kardina Simamora; Adelina Lubis; Hery Syahrial; Ihsan Effendi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This study aims to determine the effect of Social Media Marketing and Brand Awareness on the intention to buy MS Glow skincare products in the millennial generation in Lubuk Pakam, a case study of the Israhayu beauty shop in Lubuk Pakam. Data collection techniques in this study used a questionnaire with a quantitative approach. The data analysis technique used was descriptive statistical analysis and multiple regression analysis, then hypothesis testing using SPSS 25. The results showed that partially Social Media Marketing had a significant positive effect on buying interest, and Brand Awareness had a positive and significant effect on Purchase Interest.